Research Hotspot and Trend of Employee Creativity Based on Bibliometric Analysis - Shi, Yang; Zhang, Hong-yuan (Frontiers in Psychology, 2022)
Employee creativity is the foundation of organizational competitiveness, and it is also the important theme of creativity research. Based on the knowledge graph theory, this article uses the Citespace software to conduct a bibliometric analysis of 1,168 importance literature from the Web of Science and draws the co-citation and co-word clustering knowledge graph to explore research hotspots and trends of employee creativity. The research found that: First, the research on the connotation, dimensions, and behavior of employee creativity is still in the initial stage; second, the research on the psychological, behavioral, and management factors that affect employee creativity is the key content of common concern; and third, it needs to comprehensively consider relevant factors from the combination of individuals, groups, and organizations about employee creativity research. On this basis, this article proposes the main directions for future research.